(untitled) (World Bulletin of Management and Law, 2024)
The article is aimed at researching the principles of architectural and artistic organization of the facades of new buildings in the historical part of Samarkand, developing the facades of buildings that reflect traditionality and modernity in our architecture, and analyzing and harmonizing the principles of the built ones.